Common Fixed Points of Two Pairs of Selfmaps Satisfying (E.A)-property in b-metric Spaces Using a New Control Function - Venkata Ravindranadh Babu Gutti; Dula Tolera Mosissa (International Journal of Mathematics And its Applications, 2017)
In this paper, we apply the (E. A)-property to prove the existence and uniqueness of common fixed points of four selfmaps in the setting b-metric spaces using a new control function. We provide an example in support of our results. Our results generalize the fixed point results of Ozturk and Radenovic [11].